Probability Liquefaction On Silty Sand Layer On Central Jakarta - Maha Agung, Putera Agung; Ahmad, Mustaffa Anjang; Rouf Hasan, Muhammad Fathur (International Journal of Integrated Engineering, 2022)
Indonesia has a strong earthquake risk. The effects of saturated silty sand liquefaction during earthquakes can be very damaging. Liquefaction is the threats to the safety of structures, and the evaluation of liquefaction potential is essential in locations with silty sand layers. Research was performed at BPJS Branch Office building project in Central Jakarta with 7 floors when conducted the substructure or deep foundation design. This research uses cone penetration test (CPT) data to evaluate the potential and probability of liquefaction. At the same time, this research also predicts the bearing capacity (Qu) of single pile embedded on silty sand layer at conditions of Non-Liquefaction (NL) and Liquefaction (L) due to an earthquake. The research results showed that silty sand layers were classified as the susceptible layers to the liquefaction potential after plotted of CPT data into the graphic from Robertson & Campanella method [1] and signed by zone A. However, bearing capacity (Qu) when condition of NL and L was only different around 10 to 11%, it can be considered that the single pile remains stable during occurrence the liquefaction and capable to support the upper structure system. This assumption is also strengthened by the analysis result of probability liquefaction (P[L]) for sand and silty sand layers, the average of (P[L]) based on the maximum earthquake acceleration (PGA) T = 50 years exists in the range < 5 % to 10 % and it can be stated that [P(L)] is very low to low [2] and it can be concluded that the sand and or silty sand layers at study area is hard to category as a liquefiable layer.